Prosa: Theorie, Exegese, Geschichte - Dell'Anno, Sina; Imboden, Achim; Simon, Ralf; Trösch, Jodok (Theorie der Prosa, 2021)
A theory of prose does not exist yet. This volume aims to free prose from its invisibility as a medium for forms or genres devoid of characteristics. It redefines prose as a structure that works in latency, as a mysterious movement, but above all as poetic self-reference. These contributions combine this interest with in-depth exegeses on texts by Joyce, Mayröcker, Wühr, Lentz, and others.